Efektivitas Wayang Golek Sebagai Media Dakwah Dalam Pengajaran Agama Islam - Aisyah Qonita; Raisya Restu Gustina; Rissella Putria; Widi Utari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Studies have been found that the use of puppet golek asa local Apache medium and thus is easy for the public to accept. What is more, wayang gave the public enthusiastic and entertained with its unique and different variations. Not only that, wayang from sundanese society was particularly relevant to the culture. Wayang was effective as the dakwah media not only spreading Islam but also entertaining the people. But it was undeniable that the puppet show had its advantages and its drawbacks.